Saff straight line detector/ Muhammad Anas Mohd Rosli ...[et al.] - Mohd Rosli, Muhammad Anas; Zaidi, 'Iffah Athirah; Ibrahim, Akmal Najihah; Aris, Mohd Aziz (2018)
Saff is all about the important aspect before starting the Solat. But nowadays, most of the Muslim people do not take care enough about the straightness of the Saff before began the Solat. To solve this problem, we came up with the idea to produce a device to enlighten the Muslim people about the Saff. Saff Straight Line Detector is being produce to help the user to know whether the Saff already straight or not. The main component of the Saff detector are IR sensor, Led, potentiometer, IC LM358 and Arduino Uno. IR sensor is the most important component since it will detect the users’ feet and send the signal to the LED. When any obstacle is being near to the IR sensor, the amount of voltage at the resistor increase. IC LM358 is used to compare the sensor and references voltages. The input will turn on when the voltage at the non-inverting input is more than the voltage at inverting input of the IC.